Phytochemical Test and Antioxidant Activity of Aqueous Extract of Marigold Flower - I Made Merdana; Indira Laksmi Nandita; Pingkan Elia; Ida Ayu Pasti Apsari; I Wayan Gorda; Luh Made Sudimartini (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Natural medicines are increasingly in demand for safety reasons and are believed to be able to cure certain diseases. Literacy reveals that the marigold flower (Tagetes erecta L.) has medicinal potential as an antioxidant, anti-bacterial, anti-inflammatory, and anti-carcinogen. This research aimed to identify marigold flower aqueous extract's phytochemical content and antioxidant activity. The method used in this exploratory research was the maceration of marigold flower simplicia using distilled water for 24 hours, followed by evaporation to obtain marigold flower aqueous extract. Then, phytochemical screening and antioxidant bioactivity tests were carried out using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The results of phytochemical screening showed that marigold flower water extract contained flavonoids, phenols, alkaloids, and tannins. Meanwhile, the antioxidant activity test obtained an IC50 value of 50.77 ppm. From these results, it can be concluded that the aqueous extract of marigold flowers has medicinal potential with vigorous antioxidant activity.